2016
DOI: 10.1002/jobm.201600091
|View full text |Cite
|
Sign up to set email alerts
|

Comparative proteome analysis reveals proteins involved in salt adaptation in Photobacterium damselae subsp. piscicida

Abstract: Proteomic approaches were applied to investigate whether Photobacterium damselae subsp. piscicida (Phdp) can directly sense and respond to growth conditions under different salinities, 0.85% and 3.5% NaCl concentrations, mimicking the osmotic conditions in host and marine water bodies, respectively. Proteins significantly altered were analyzed by two-dimensional gel electrophoresis (2-DE), liquid chromatography-electrospray ionization-quadrupole-time-of-flight tandem mass spectrometry (LC-ESI-Q-TOF MS/MS) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The enhanced expression of these gene categories was also observed in P. damselae subsp. piscicida when shifting from low to high salt ( 61 ) and in E. coli in response to growth in seawater ( 55 ).…”
Section: Resultsmentioning
confidence: 99%
“…The enhanced expression of these gene categories was also observed in P. damselae subsp. piscicida when shifting from low to high salt ( 61 ) and in E. coli in response to growth in seawater ( 55 ).…”
Section: Resultsmentioning
confidence: 99%
“…DYB exposed to hyperhaline versus hypohaline fluctuation, probably due to differences in the regulation mechanism. It has previously been shown that microorganisms have developed a range of strategies for acclimation to both low and high salt concentrations . It was also reported that the copepod Eurytemora affinis exhibits lower survival and longer development times when reared at low salinity compared to individuals reared at higher salinities .…”
Section: Discussionmentioning
confidence: 99%